The Pros and Cons of Moderna Vaccine, the COVID-19 Vaccine – a Survey Based Study - Alam, Samina; Qureshi, Nousheen; Noor, Munazza; Gulfam, Neha; Ashraf, Iqra; Iftikhar, Ghazal; Raza, Rashid (Journal of Research (Science), 2025)
Introduction: During emergency situation of COVID-19 panademic Moderna vaccines was authorized by food and drug administration under emergency use authorization (EUA) this survey manifests different peoples openion and their experience upon Moderna vaccination Objective: This survey was carried out to find out the pros and cons of the vaccination carried out for COVID-19 by Moderna vaccine. Method: In the preparation of this survey based article we made google form and set questions related to Moderna vaccine and individual openion on it, distributed to 100 participants and gather all material we have searched WHO guidelines and study EUA fact sheet provide by FDA go read different articles included google scholar ,Pub med, Science Direct , ELSEVIER, ResearchGate etc. Results: Based on the survey article, Moderna vaccine has been proven safe and effective against SARS-COVID-2. The vaccine was recommended to apply on 18 or above years of aged persons. It shows immunity for at least 119 days after the first vaccination and is 94.5% effective however. Some of the vaccinated persons found to be associated with allergic symptoms such as Covid arm, fever, muscle pain, tiredness and chills. However, no severe adverse effect of this vaccine has still been reported. Conclusion: It has been concluded that the Moderna vaccine is perfectly safe and effective against the COVID-19 pandemic. The vaccine is also found to be more potent with only a few side effects such as swelling and pain at the administration side only.